Analisis Cemaran Escherichia coli pada Sampel Makanan Menggunakan Metode Compact Dry - Warda Amalia; Endang Sulistyarini Gultom Endang Sulistyarini Gultom (Universitas Cokroaminoto Palopo, 2026)
Food safety is a critical aspect of protecting public health from foodborne diseases caused by microbiological contamination, with Escherichia coli serving as a key indicator of food hygiene and sanitation. This study aimed to analyze Escherichia coli contamination in food samples using the Compact Dry method and to evaluate its compliance with food safety standards. A descriptive method with a quantitative approach was employed on 20 food samples, which were tested using Compact Dry EC and incubated at 36 ± 0.5°C for 21 ± 2 hours. The results were expressed in CFU/g and compared with the standards set by SNI 7388:2009. The findings showed that 45% of the samples were positive for Escherichia coli, with contamination levels ranging from <1 to 1.25 × 10³ CFU/g, while 55% were negative. All positive samples did not meet food safety standards. Contamination was likely due to poor hygiene and sanitation practices, including cross-contamination during food processing and handling. The Compact Dry method proved to be effective, practical, and efficient for detecting Escherichia coli. These findings indicate that microbiological contamination in food remains a concern, highlighting the need to improve hygiene and sanitation practices to ensure food safety.